The Relationship Between TQM Practices and Primary School Academic Performance in Abu Dhabi: Innovation as a Mediator - Alhosani, Mohamed Salem; Dr. Kamarul Bahari Bin Yaakub (European Journal of Multidisciplinary Studies, 2020)
The main purpose of this study was to examine total quality management practices and primary school academic performance in Abu Dhabi: innovation as a mediator. A quantitative research design was utilized. A total of 342 teachers will be chosen as a sample through a simple random sampling technique. Data analysis using structural equation modelling will be used. There will be significant relationship between total quality management practices and primary school academic performance; total quality management practices and innovation; innovation and primary school academic performance; significant contribution of mediating role of innovation on the association between total quality management practices and primary school academic performance; significant contribution of mediating role of innovation on the association between total quality management practices and primary school academic performance and significant role of innovation dimensions on the primary school academic performance. Presentation of data analysis and discussion of findings will be given after the completion of chapter four and five. It is hope of this study that TQM practices will be used by schools in Abu Dhabi region to improve primary school’s academic performance.